PENGARUH PERHATIAN ORANG TUA TERHADAP HASIL BELAJAR PESERTA DIDIK MATA PELAJARAN IPS KELAS VII - Khasandra Egi Aultama; Aminuyati Aminuyati; Husni Syahrudin (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
Abstract The purpose of this research was to determine how much influence between the attention of parents with learning outcomes of students of class VII IPS at SMP Negeri 20 Pontianak. The research method that used is descriptive quantitative research. The sample in the study was 66 grade VII students taken at random (Simple Random Sampling) and the data were questionnaire statements about the attention of parents with 5 indicators namely providing guidance and advice, supervising children, giving awards and punishment, fulfilling facilities learning, and creating a calm, comfortable and peaceful home atmosphere. Based on the results of data analysis conducted by researchers concluded that: 1) the attention of parents show results with 78.8% (52 students) have a medium category. 2) IPS learning outcomes obtained by 71.2% (47 students) have a medium category. 3) The influence of parental attention with learning outcomes is 0.791 with a significant standard level of 0.05 (5%). So that the results of arithmetic > t table are 11,124> 1,999 From the results of the study it can be concluded that there is a positive influence between parents attention to the learning outcomes of VII grade students of SMP Negeri 20 Pontianak in IPS. Keywords: Parental Attention, Learning Outcomes, IPS